All‐Inorganic Quantum‐Dot LEDs Based on a Phase‐Stabilized α‐CsPbI3 Perovskite. Issue 29 (14th June 2021) - Wang, Ya‐Kun; Yuan, Fanglong; Dong, Yitong; Li, Jiao‐Yang; Johnston, Andrew; Chen, Bin; Saidaminov, Makhsud I.; Zhou, Chun; Zheng, Xiaopeng; Hou, Yi; Bertens, Koen; Ebe, Hinako; et al.
Abstract: The all‐inorganic nature of CsPbI3 perovskites allows to enhance stability in perovskite devices. Research efforts have led to improved stability of the black phase in CsPbI3 films; however, these strategies—including strain and doping—are based on organic‐ligand‐capped perovskites, which prevent perovskites from forming the close‐packed quantum dot (QD) solids necessary to achieve high charge and thermal transport. We developed an inorganic ligand exchange that leads to CsPbI3 QD films with superior phase stability and increased thermal transport. The atomic‐ligand‐exchanged QD films, once mechanically coupled, exhibit improved phase stability, and we link this to distributing strain across the film. Operando measurements of the temperature of the LEDs indicate that KI‐exchanged QD films exhibit increased thermal transport compared to controls that rely on organic ligands. The LEDs exhibit a maximum EQE of 23 % with an electroluminescence emission centered at 640 nm (FWHM: ≈31 nm). These red LEDs provide an operating half‐lifetime of 10 h (luminance of 200 cd m −2 ) and an operating stability that is 6× higher than that of control devices. Abstract : Stable and efficient CsPbI3 perovskite light‐emitting diodes (PLEDs) are demonstrated by resurfacing perovskite with the aid of inorganic ligands (KI). The resurfaced perovskites show a 7× higher phase stability and higher thermal conductivity than in films with organic ligands. The PLEDs exhibit a record‐high external quantum efficiency (EQE) of ≈23 % and a 100‐fold improvement in the operating stability compared to previous EQE devices.